Menganalisis Perspektif Nilai Manajemen Sumber Daya Manusia untuk Menghadapi Era Society 5.0 - Sinthia, Ine; Solihat, Solihat; Suharyat, Yayat (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research discusses the value of human resource management in facing the era of society 5.0. This research is a literature research with descriptive analysis approach. The object of this research is human resource management, while the data sources used are all literature on human resource management and the development of the era of society 5.0. The data is then collected and processed into study results. Data validity is carried out by triangulating sources, namely comparing data obtained from various sources. This research shows that human resource management is needed in facing the society 5.0 era. The idea of the society 5.0 era as the next movement after the industrial revolution 4.0 era requires humans to always be ready for all its challenges. This is because humans will be the center of all civilization in the era of society 5.0. Things that need to be prepared to welcome the era of society 5.0 include knowing the challenges of the era of society 5.0, carrying out good management of human resources, knowing the stages of HR planning, and knowing the developments that must be carried out to improve the quality of human resources.